Analysis of Pomegranate Dye Coated Titanium Nanotubes Anode for Solar Cell Application - P. Thenmozhi; P. Sathya; S. Meyvel; Subash Thanappan (Advances in Materials Science and Engineering)
The titanium nanotube array is termed as titanium nanotubes anode (TNTA). Initially, four samples of TNTA were synthesized using electrochemical anodization method. The titanium nanotube arrays (TNAs) were fixed as anode for dye-sensitized solar cell application. The execution of dye-sensitized solar cells (DSSCs) is found on natural dyes removed out from natural materials. Then, pomegranate dye was exclusively prepared and coated on TNTA samples. These are very affordable and inexpensive and are abundantly available in India. The dye coated TNTAs were distinguished using UV-viewable spectrophotometer and SEM test for their spectral effects. The natural dye showed a wide-ranging absorption performance peak between 300 and 574 nm for the second sample and 300–572 nm for third sample. Their solar absorption property was studied.